Disaggregate Energy Consumption and Total Factor Productivity: A Cointegration and Causality Analysis for the Turkish Economy. - Tugcu, Can Tansel (International Journal of Energy Economics and Policy, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false TR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:TR; –> <!–[endif] –> The aim of this study is to investigate the long and the short-run relationships between disaggregate energy consumption (i.e. alternative and nuclear, fossil and renewable) and total factor productivity growth in the Turkish economy for the period 1970-2011. To this end, ARDL bounds testing approach to cointegration and the Dolado and Lütkepohl’s Granger causality analyses were employed. Results showed that disaggregate energy consumption is cointegrated to total factor productivity growth and there exists bi-directional causal relationships among the variables in consideration. Besides, findings revealed that the share of renewable energy consumption in total energy consumption is the only energy type which positively affects total factor productivity growth in the Turkish economy. This result implies that an improvement in the share of renewable energy consumption in total energy consumption is crucial for economic efficiency. Keywords: Disaggregate energy consumption; Total factor productivity growth; Turkish economy. JEL Classifications: C33; O47; O50; Q20; Q30; Q40